Character Building Through Reinforcement of Islamic Learning - Nurbaiti Nurbaiti; Mundzier Suparta; Taufik Abdillah Syukur (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractThis research explores the effects of teacher’s pedagogical competence and student’s achievement to student’s character building. The research method used is mixed method. Data collected by test, questionnaire, interview and observation. Data analyzed by bivariate correlation and Triangulation. The result of this study proved that character building through reinforcement of Islamic learning is effected by the teacher’s pedagogical competence and student’s achievement.AbstrakTujuan dari penelitian ini adalah untuk mengetahui bagaimana kompetensi pedagogik guru dan prestasi belajar siswa mempengaruhi pembentukan karakter siswa. Metode penelitian yang digunakan adalah metode penelitian campuran (Mixed Method). Pengumpulan data dilakukan melalui tes, angket, wawancara dan pengamatan (observasi). Analisis data dilakukan  dengan korelasi ganda dan triangulasi. Dari hasil penelitian diperoleh hasil bahwa pendidikan karakter siswa dipengaruhi oleh kompetensi pedagogik guru dan prestasi belajar siswa pada Mata Pelajaran Pendidikan Agama Islam. How to Cite : Nurbaiti, Suparta, M., Syukur, T. A. (2019).  Character Building Through Reinforcement of Islamic Learning. TARBIYA: Journal of Education in Muslim Society, 6(1), 36-45. doi:10.15408/tjems.v6i1.10984.